Association between cardiometabolic index and congestive heart failure among US adults: a cross-sectional study - Luo, Xi; Cai, Bin (Frontiers in Cardiovascular Medicine, 2024)
The risk of congestive heart failure (CHF) is significantly affected by obesity.However, data on the association between visceral obesity and the risk of CHF remain limited. We explored the relationship between CHF and cardiometabolic index (CMI). Drawing from the National Health and Nutrition Examination Survey (NHANES) for 2011-2018, we enrolled 9,008 participants in a cross-sectional study. we evaluated the relationships between CHF nda of CMI and CMI-age with CHF, To examine the predictive ability of CMI and CMI-age on patients with CHF. The results revealed significant differences in demographic data among the groups classified by CMI and CMI-age quartiles. When indicators were analyzed as continuous variables, CMI and CMI-age showed positive correlations with CHF in both the crude and adjusted models (all P < 0.05). When indicators were analyzed as categorical variables, it was found that in all four models, the ORs of group Q4 was significantly different compared to Q1 (all P < 0.05). The associations of CMI and CMI-age with CHF were similar in all stratified populations (P for interaction > 0.05). The incidence of CHF in Q1 CMI was significantly lower than that in Q4 (Q1 vs. Q4: OR = 1.65, 95% CI: 1.11-2.44). The multivariate logistic analysis results showed that no significant interactions existed between CMI and demographic data, BMI, lifestyle variables, diabetes, and hypertension. The relationship between the CMI and CHF showed an increased dose response, and the area under the ROC curve (AUC) of CMI for the identification of CHF was 0.610 (95% CI: 0.578-0.642).The areas under the ROC curve (AUCs) of CMI and CMI-age in predicting CHF were 0.610 (95% CI, 0.578-0.642) and 0.697 (95% CI, 0.668-0.725) separately, suggesting that CMI-age was significantly better than the CMI in predicting CHF (P<0.001).Both CMI and CMI-age were was independently correlated with the risk for CHF.These results suggested that the CMI-age, which provides new insights into the prevention and management of CHF. CMI-age with simpler parameters, could serve as effective tools to identify CHF during primary care examinations and in medically resource-limited areas.